Effects of calcium alginate-rich Undaria pinnatifida (Wakame) powder on postprandial glycemia and insulin levels in healthy individuals: a randomized, double-blind, placebo-controlled crossover trial - Keiko Yoshinaga; Rieko Mitamura (Food, Nutrition and Health, 2026)
Abstract Postprandial hyperglycemia is a known risk factor for several health disorders, including type 2 diabetes, obesity, and cardiovascular disease. This study investigated the acute effects of calcium alginate-rich Undaria pinnatifida (Wakame)—a characteristic constituent of the Japanese diet—on postprandial blood glucose and insulin levels. Twenty-two healthy Japanese individuals were enrolled in this randomized, double-blind, placebo-controlled crossover study. The eligible participants were aged 20–59 years and had a fasting blood glucose level < 125 mg/dL at the preliminary examination. Blood samples were collected for glucose and insulin measurements at 0, 30, 60, 90, and 120 min after participants consumed either 150 g of rice with 100 g of curry alone or the same meal supplemented with 2 g of calcium alginate–rich Wakame powder. Blood glucose and insulin levels were respectively 7 mg/dL and 7.5 μU/mL lower ( p < 0.05) at 30 min after consuming rice and curry supplemented with Wakame powder than after consuming rice and curry alone. The incremental areas under the curves for insulin at 0–60 min were lower ( p < 0.05) when Wakame powder was included. In the artificial digestion test, the glucose concentration at 20 min was lower than that in the control (252 ± 8.9 mg vs 279 ± 6.7 mg, p < 0.05). These results indicate that consuming Wakame powder with food staples, such as rice and curry, may be effective for attenuating postprandial glycemic excursions. This study was registered in the UMIN Clinical Trial Registry (UMIN000052681, November 6, 2023).